Single-Anastomosis Duodenal Jejunal Bypass Improve Glucose Metabolism by Regulating Gut Microbiota and Short-Chain Fatty Acids in Goto-Kakisaki Rats - Yu, Xiang; Wu, Zhuangwei; Song, Zhigao; Zhang, Hongbin; Zhan, Junfang; Yu, Hao; Huang, Hongyan; Yang, Baolin; Xie, Lang; Dai, Xiaojiang; Zhao, Weiguo; Yu, Jinlong; et al. (Frontiers in Microbiology, 2020)
In recent years, bariatric surgery has emerged as a promising treatment for type 2 diabetes. Bariatric surgery is known to cause alterations in the relative abundance and composition of gut microbiota, which may lead to alterations in the levels of Short-Chain Fatty Acids (SCFAs) that are produced during fermentation by gut microbes. However, little is known about the mechanism of improved glucose metabolism mediated by gut microbiota following bariatric surgery. The aim of our study was to explore whether changes in gut microbiota and in fecal SCFA could be detected following single-anastomosis duodenal jejunal bypass (DJB-sa) surgery, a type of bariatric surgery, and whether these alterations might be related to the improvement of glucose metabolism. To this end, we performed DJB-sa or SHAM surgery on Goto-Kakisaki (GK) rats. We then compared the glucose metabolism as well as changes in gut microbiota and SCFAs levels between both groups. Our results showed that DJB-sa surgery was associated with a significant decrease in fasting blood glucose (FBG), intraperitoneal glucose tolerance test (IPGTT), and fasting serum insulin (FSI). And, DJB-sa led to a change in the composition of gut microbiota including an increase in the relative abundance of SCFA-producing bacteria (Bifidobacterium and Subdoligranulum). Moreover, the levels of six SCFAs in feces, as well as the intestinal expression of SCFA receptors including G-protein-coupled receptor 41 (GPR41), G-protein-coupled receptor 43 (GPR43), and G-protein-coupled receptor 109A (GPR109A), and the expression of Glucagon-like peptide-1 (GLP-1) displayed a significant increase following DJB-sa compared with the Sham group. Thus, the gut microbiota may contribute to the improvement of glucose metabolism in type 2 diabetes following DJB-sa. In conclusion, our study shows that DJB-sa improves glucose metabolism by modulating gut microbiota and by increasing short-chain fatty acid production.